Optimalisasi Smart Economy dalam Kenaikan Daya Saing UMKM Kota Bandung - hariyatna syaeful umam; Ade Yunita Mafruhat (UNISBA Press, 2023)
Abstract. The purpose of this study is to analyze how to optimize the smart economy in empowering MSMEs in order to increase MSMEs competitiveness in the city of Bandung. The type of research used is descriptive research with a qualitative approach. The results of this study, the Bandung City government already has a strategy in optimizing the smart economy in empowering MSMEs, it is well seen that there are many actors who have taken part in the implementation of the smart economy program. Through a SWOT analysis, quadrant I shows the position of the MSMEs optimization strategy and the S-O strategy position is used, namely utilizing the image of the City of Bandung as a city with smart economy and government support to increase the competitiveness of MSMEs. Abstrak Tujuan penelitian ini adalah untuk menganalisis bagaimana optimalisasi smart economy dalam pemberdayaan UMKM guna peningkatan daya saing UMKM di Kota Bandung. Jenis penelitian yang digunakan yaitu jenis penelitian deskriptif dengan pendekatan kualitatif. Hasil dari penelitian ini pemerintah Kota Bandung sudah memiliki strategi dalam mengoptimalisasikan smart economy dalam pemberdayaan UMKM dengan baik dilihat dengan ada banyak pelaku UMKM yang sudah ikut andil dalam pelaksanaan program smart economy. Melalui analisis SWOT, kuadran I menunjukkan posisi strategi optimalisasi UMKM dan pada posisi tersebut digunakan strategi S-O yaitu memanfaatkan image Kota Bandung sebagai kota dengan ekonomi cerdas dan dukungan pemerintah guna meningkatkan daya saing UMKM